Development of a truck chassis - Abdul Rahman, Roslan; Yusof, Mustafa; Tamin, Mohd. Nasir (Faculty of Mechanical Engineering, 2009)
Truck chassis is a major component in a vehicle system. This work involved static and dynamics analysis to determine key characteristics of a truck chassis. The static characteristics include identifying location of high stress area and determining the torsion stiffness of the chassis. The dynamic characteristics of truck chassis such as the natural frequency and mode shape were determined by using finite element method. Experimental modal analysis was carried out to validate the FE models. Modal updating of truck chassis model was done by adjusting the selective properties such as mass density and Poisson’s ratio. Predicted natural frequency and mode shape were validated against experimental results. Finally, the modifications of the updated FE truck chassis model was proposed to reduce the vibration, improve the strength, and optimize the weight of the truck chassis. The major areas of concern in the truck chassis were found to be coincidence of a structural resonance at 52 Hz, experienced the torsional and bending mode. Modifications to shift natural frequencies were proposed by increasing thickness of the chassis center section by 2 mm and additional of stiffeners member located at center of the base plate by 10 mm. In addition, the overall modifications carried out from analysis were successfully achieved with the natural frequency had shifted by 13 % higher than the original value, increased the torsion stiffness by 25 % and reduced the total deflection by 16 %. The overall weight of new truck chassis had increased by 7%.